A legitimação da pena e dos seus equivalentes funcionais no direito penal negocial - Gomes Filho, Dermeval Farias (2023)
The expansion of negotiated criminal justice institutes is one of the effects of the expansion of the space for criminal protection during the second half of the 20th century. The instruments of negotiated criminal justice, classified into sentencing agreements and diversion agreements, coexist with the trial solution in different procedural systems, anchored in dispute or official investigation models. The reduction of the penalty below the abstract minimum, the modification of the typicity of the fact committed and the adoption of functional equivalents of the penalty, in criminal agreements, imply the need to seek the legitimization of the criminal response within the scope of negotiated criminal law. The classical theories of punishment find it difficult to justify the responses produced in criminal agreements. The research demonstrates, through bibliographic, documental and empirical analysis of procedural data, how little space theories of punishment have for negotiated criminal justice. The comparison between criminal plea bargains in different legal systems indicates the absence of a literal importation of the American plea bargain. Negotiated criminal law allocates greater decision making space to the Public Prosecutor's Office and, for this reason, there is a need for more uniform guidelines for action. In the apparent tension between negotiated criminal justice and victim rights, research indicates that victim satisfaction is related to their desire and ability to participate, and that they do not necessarily seek veto power over the prosecutor's choice. From the dogmatic aspect, the legitimization of the criminal response in sentencing agreements aligns, with difficulty, with preventive theories. In a political-criminal conception, the justification is grounded in the Economic Analysis of Law, in faster procedures and cost reduction. The principles of legality and the legal reserve offer a foundation for the legitimization of criminal agreements when there is a correspondence between the fact committed and the accused. In reduced sentence agreements, which require a voluntary and intelligible confession, made between the prosecution and the defense, with reparation for the damage and the victim's right of conference, there is greater procedural efficiency and, likewise, the capacity to communicate the adequate penal response to the victim and to society, besides dialoguing with some of the effects proclaimed by the classical theories of punishment. The research points to the legitimization of the functional equivalent of the penalty in the effective communication to the offender, the victim and society. For this construction, it presents the sufficient protection of the protected legal good anchored in the theory of constitutional mandates of criminalization. Likewise, it makes possible the construction of a criminal law without concrete punishment for less intense offenses in stages of criminal prosecution that precede the formation of guilt. Finally, it relates the criminal response through functional equivalents of the penalty as a political-criminal alternative to reduce incarceration and contribute to the balanced management of the Brazilian prison system